2020
DOI: 10.2147/ndt.s239013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differentiating Boys with ADHD from Those with Typical Development Based on Whole-Brain Functional Connections Using a Machine Learning Approach</p>

Abstract: In recent years, machine learning techniques have received increasing attention as a promising approach to differentiating patients from healthy subjects. Therefore, some resting-state functional magnetic resonance neuroimaging (R-fMRI) studies have used interregional functional connections as discriminative features. The aim of this study was to investigate ADHD-related spatially distributed discriminative features derived from wholebrain resting-state functional connectivity patterns using machine learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…Besides, some authors argue that the cerebellum may control the cognitive development of the child by guiding the maturation of diffuse brain circuitry (Wang et al., 2014). In this line, the recent (Sun et al., 2020) demonstrated with the use of a support vector machine applied on fMRI signals that the functional connections between the cerebellum and fronto‐parietal cortex provide the most discriminative power in ADHD versus. TDC classification.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some authors argue that the cerebellum may control the cognitive development of the child by guiding the maturation of diffuse brain circuitry (Wang et al., 2014). In this line, the recent (Sun et al., 2020) demonstrated with the use of a support vector machine applied on fMRI signals that the functional connections between the cerebellum and fronto‐parietal cortex provide the most discriminative power in ADHD versus. TDC classification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sutcubasi and colleagues (Sutcubasi et al, 2020) found that ADHD was associated with a connectivity disruption within the DMN than HC. Sun and colleagues (Sun et al, 2020) et al, 2012) found decreased fALFF in the medial prefrontal and orbitofrontal cortices and DMNs in bilateral putamen with increased rsFC in the left insula and bilateral dorsal prefrontal cortex. In SCHZ, ALFF was reduced in the bilateral ventral frontal cortex (Lui et al, 2010).…”
Section: Adhd and Hcmentioning
confidence: 99%
“…Previous studies have suggested that functional interactions in large-scale brain networks could be utilized for the classification of patients vs. healthy subjects. For example, interregional functional connections were regarded as discriminative features of support vector machine (SVM) to differentiate patients diagnosed with attention deficit hyperactivity disorder (ADHD) from healthy subjects (Sun et al, 2020 ). Whole-brain functional connections were also adopted as features of SVM to identify patients with schizophrenia (Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been regarded as an exploratory framework to characterize the brain functional organization from interregional functional connections that may be implicated in neuropathology underlying neuropsychiatric disorders. For example, the cerebellum showed high discriminative power for identifying patients with ADHD (Sun et al, 2020 ). The functional connections across the DMN and visual cortical areas showed high discriminative power when discriminating major depressive patients from healthy subjects (Zeng et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%